ANALISIS PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN DAN LOYALITAS PASIEN DI POLIKLINIK PT. GUDANG GARAM TBK. KEDIRI - Meliana Susanti (Universitas Islam Kadiri, 2020)
In this study discussed the relationship between service quality, satisfaction and patient loyalty in the clinic of PT. Gudang Garam Tbk. The purpose of this study was : 1. To determine the effect of service quality to patient satisfaction in the clinic of Gudang Garam 2. To determine the effect of service quality to patient loyalty in The clinic of Gudang Garam. 3. To determine The effect ofpatient satisfaction to patient loyalty in the clinic of Gudang Garam. This Type of Research is quantitative descriptive. The approach used for data analysis is a quantitative analysis using SEM (Structural Equation Modeling) with the help of Sofware Warp PLS (Partial Least Square) 4.0. The Population used was a patient who came to the clinic for treatment of at least two visits with the level of senior high school education/equivalent. The total sample of 100 respondents. Sampling technique used non probability sampling is that accidental sampling. The Results showed that there was positive and significant influence between the quality of service to patient satisfaction, service quality to patient loyalty and patient satisfaction to patient loyalty in the clinic of Gudang Garam Kediri. In conclution, the management of the clinic of Gudang Garam should routinely give attention to the quality of Service is maintained and even improved, which will increase patient satisfaction and patient loyalty in the clinic of Gudang Garam Kediri.